Heritable Genomic Fragment Deletions and Small Indels in the Putative ENGase Gene Induced by CRISPR/Cas9 in Barley - Kapusi, Eszter; Corcuera-Gómez, Maria; Melnik, Stanislav; Stoger, Eva (Frontiers in Plant Science, 2017)
Targeted genome editing with the CRISPR/Cas9 system has been used extensively for the selective mutation of plant genes. Here we used CRISPR/Cas9 to disrupt the putative barley (Hordeum vulgare cv. “Golden Promise”) endo-N-acetyl-β-D-glucosaminidase (ENGase) gene. Five single guide RNAs (sgRNAs) were designed for different target sites in the upstream part of the ENGase coding region. Targeted fragment deletions were induced by co-bombarding select combinations of sgRNA with wild-type cas9 using separate plasmids, or by co-infection with separate Agrobacterium tumefaciens cultures. Genotype screening was carried out in the primary transformants (T0) and their T1 progeny to confirm the presence of site-specific small deletions and insertions (indels) and genomic fragment deletions between pairs of targets. Cas9-induced mutations were observed in 78% of the plants, a higher efficiency than previously reported in barley. Notably, there were differences in performance among the five sgRNAs. The induced indels and fragment deletions were transmitted to the T1 generation, and transgene free (sgRNA:cas9 negative) genome-edited homozygous ENGase knock outs were identified among the T1 progeny. We have therefore demonstrated that mutant barley lines with a disrupted endogenous ENGase and defined fragment deletions can be produced efficiently using the CRISPR/Cas9 system even when this requires co-transformation with multiple plasmids by bombardment or Agrobacterium-mediated transformation. We confirm the specificity and heritability of the mutations and the ability to efficiently generate homozygous mutant T1 plants.